Exploring Inductive Reasoning, Scientific Reasoning and Science Motivation, and Their Role in Predicting STEM Achievement Across Grade Levels - Vo Van De (INTERNATIONAL JOURNAL OF SCIENCE AND MATHEMATICS EDUCATION, 2023)
This study aims to investigate the patterns of students’ performance in inductive reasoning, scientific reasoning and science motivation at different grade levels. We also examined the interaction of these variables with parental factors in predicting students’ STEM achievement. A cross-sectional study assessed 726 participants from the 6 th , 8 th , 10 th and 11 th grades in 6 secondary schools. The findings showed that students in the upper grades achieved higher scores on reasoning tests than their counterparts in the lower-grade cohorts, but their motivation toward learning science decreased slightly across the grade cohorts. Although the students performed better on an inductive reasoning test, the developmental patterns were comparable for the results on 2 cognitive tests across grade levels. Generally, we found that inductive reasoning and scientific reasoning were closely tied and that both had a significant effect on STEM achievement, while parents’ education impacted positively on both STEM performance and parental involvement in their children’s schooling. However, parental involvement and science motivation had a minor—and different—influence on students’ STEM achievement in the individual grade cohorts. The implications for enhancing students’ STEM performance are further discussed accordingly.